The obligation of “saksama” in article 16 of the Law on notary positions: a perspective on the principle of diligence in partij deed (Law and Safety, 2024)
This study analyzes the implementation of the principle of “due care” as stipulated in Article 16 of Law No. 2 of 2014 concerning the Position of Notary. This principle requires notaries to act with high levels of diligence, honesty, and integrity in carrying out their duties. The objective of this research is to explore the normative, substantive, and practical meanings of the principle of “due care” and to identify challenges in its implementation. Employing normative legal research methods, this study integrates a statutory approach to understand the normative framework of the regulation and a hermeneutic approach to interpret the social context and legislative intent. The analysis technique used is content analysis of legal documents, academic literature, and relevant court decisions.The findings reveal that the implementation of the principle of “due care” faces challenges such as the lack of operational definition, limited technical competence of notaries, and weaknesses in supervisory mechanisms. These issues can lead to varying interpretations and risks of violations by notaries. This study recommends regulatory reforms to clarify the legal boundaries of the “due care” principle, the development of continuous training to enhance notary competence, and the strengthening of technology-based supervision and periodic audits.In conclusion, reforms in regulation, education, and supervision are necessary to ensure the consistent application of the principle of “due care”. This research provides practical and theoretical contributions by offering strategic steps to strengthen the integrity of the notary profession and increase public trust in Indonesia’s legal system.
Keywords: due care principle; notary position; hermeneutic approach; legal regulation; supervision mechanisms; legal system; public trust.